El mito del guerrillero: El Empecinado de Pérez Galdós - María de los Ángeles Ayala Aracil (Cuadernos de Ilustración y Romanticismo)
In this article we will discuss how Galdós in El Empecinado contemplates the phenomenon of the guerrilla, what were the motivations that led the people of the village to take up arms and the consequences that this irregular war caused in later Spanish society.